Analisis Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Kantor Camat Kecamatan Bubon Kabupaten Aceh Barat - Afifah Afifah; Damrus Damrus (Universitas Teuku Umar, 2021)
Abstract This study aims to determine the influence of organizational culture on the performance of the sub-district office employee of Bubon District, this research was conducted in May-July 2021. The research method used was a descriptive qualitative method with data collection techniques including in-depth interviews, observations, and documentation studies. . The results of this study the author can describe the influence of organizational culture on the performance of the employees of the sub- district office of Bubon. Informant retrieval in this study was carried out in two ways, namely Main Informants and Supporting Informants. The Main Informants (IU) are the Head of the Bubon Subdistrict and the Supporting Informants consisting of IP1 Secretary of the Camat, IP2 Head of Administration, IP3 Social Welfare Staff, and IP4 Freelance Daily Workers (THL). The results of this study indicate that from several indicators of organizational culture in the sub-district office of Bubon it is known that organizational culture can affect employee performance, seen from habits, regulations and values. (1) The habits of employees at the Bubon sub-district office are still not good where they have not been disciplined about their respective responsibilities and duties, (2) the regulations at the Bubon sub-district sub-district office have not been fully implemented optimally, (3) the values at the office The sub- district head of the Bubon sub-district is considered very important because it is closely related to the quality and quantity of performance. Keywords: Organizational Culture, Employee Performance of the Sub-District Office.